Study of the undergraduated student satisfaction at quantitative content subjects - Martin Caraballo, Ana M.; Paralera Morales, Concepción; Ramírez Hurtado, José M. (IJERI: International Journal of Educational Research and Innovation, 2021)
After the implementation of the European Higher Education Area many changes has been carried out at University. With this new system the students become a main character of themselves learning due to their active and continued participation in the system. Thus, the study of student satisfaction is a main objective in order to detect some defects in the development of the teaching. Also, one of our goals is to study if there are differences in the perception that the students have about the teaching of these subjects in different Spanish universities. In order to do this, a variant of the traditional importance-valuation model will be used. This paper deals with the measure of the satisfaction of the undergraduate students having quantitative content subjects at Business Faculties. In order to do this, a variation of the traditional importance-performance analysis is used. In general, the results show that students have a minimum degree of dissatisfaction with all the attributes, although the degree of satisfaction is not too high. Furthermore, between the different universities there exist significant differences when we study the perception (and understanding) of the students of some aspects of the teaching of these subjects.